-3x + b = 6x
asked Aug 23, 2011 in Algebra 1 Answers by gatorhead (120 points)

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:

To avoid this verification in future, please log in or register.

1 Answer

-3x + b = 6x
1. Add 3x to each side of equation
-3x + 3x + b = 6x + 3x
b = 6x

2. Divide by 6 to each side of equation
(b/6) = (6x/6)
(b/6) = x

x = b/6
answered Aug 25, 2011 by VOLTAGEM (460 points)

Related questions

Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
79,835 questions
83,674 answers
66,580 users